A review of the shear rheology of carbon black suspensions - Richards, Jeffrey J.; Ramos, Paolo Z.; Liu, Qingsong (Frontiers in Physics, 2023)
The microstructural link to the rheology of carbon black suspensions has recently become clear as a result of advances in computational and experimental methods. This understanding reveals the important role of the restructuring, build-up, and break-down of carbon black agglomerates in simple shear, rationalized by a dimensionless balance of the hydrodynamic forces acting to break the agglomerates apart against the cohesive forces holding them together (i.e., the Mason number). The Mason number not only can predict the origin of reversible thixotropy seen in carbon black suspensions observed at higher shear intensities, but can also be used to rationalize the evolution of microstructure at lower shear intensities. This review focuses on carbon black suspension behavior, but the insights derived from carbon black suspensions are broadly applicable to a diverse class of soft matter including colloidal gels relevant to a variety of applications.